Resesi Ekonomi Dan Implikasinya Dari Perspektif Hukum Bisnis (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The Covid-19 pandemic has given rise to long-lasting multi-sector problems, including the economic sector, which then resulted in an economic recession and its implications. It is certainly hoped that such conditions will not occur for a long time, it is the hope of all parties including the government that the recession will soon return to normal by pursuing various steps and approaches such as the business law approach. This article focuses on studying how to photograph an economic recession and its implications from a business law perspective as an alternative to economic recovery. This research is a library research by searching literature texts related to economic recessions that focus on a business law approach. The research findings are that from a business law perspective, law is able to provide procedural solutions (procedural capability) in resolving the economic recession. Law can play a role in creating balance, because it is related to economic development initiatives. Law also plays a role in determining clear definitions and status. In the end, the law must also be able to provide a clear definition and status regarding the consequences of social interaction as well as accommodate a clear balance for the interests of individuals or groups in society.